Consumer Acceptance, Social Behavior, Driving, and Safety Issues Regarding Electric Vehicles in Oman - Sabareesaan Kannammal Jayabalan; Ahmed Said Obaid Albusaidi; Gaurav Singh Negi; Mohammed Ismail Iqbal; Hussein Al Abdulqader (World Electric Vehicle Journal)
Following Vision 2040, Oman seeks to achieve economic diversification and environmental sustainability. In this context, the world’s quest of going electric brings along opportunities as well as challenges. This study aims at determining the key barriers and facilitators of EV adoption in the country. This study examines factors such as consumer acceptance, engagement, and safe driving in relation to EVs, with a specific focus on Oman. To establish what Omani clients prefer, what worries them most, and whether they would consider making the switch to electric vehicles, empirical data on a sufficiently representative number of Omani clients were collected through a survey. According to the responses, 55% of the participants reported that they would be willing to think about purchasing an electric vehicle (EV) for their next car, which suggests a somewhat moderate level of consumer acceptance. Adoption is hindered primarily by concerns about the reliability of batteries in extreme weather conditions, high purchase prices, fear of running out of charge, and lack of sufficient charging stations. Most of the EV drivers appreciate the calm and ease of driving an electric vehicle. As the report states, certain actions must be taken, including creating public awareness through educational programs and campaigns, providing government subsidies or financial incentives, and creating the necessary infrastructure for charging equipment. To address these issues and quicken the pace of Oman’s transition to electric vehicles, this calls for collaboration among policymakers, car manufacturers, and transport planners. Aside from offering actionable recommendations regarding eco-friendly means of transport in Oman, which is relevant to the acceptance of electric vehicles in the country, this research also enhances the understanding of the issues related to the acceptance of electric vehicles in the country.